ARTIFACTS ON EEG: IDENTIFICATION AND DIFFERENTIAL DIAGNOSIS - S. A. Guljaev; I. V. Arkhipenko (Русский журнал детской неврологии, 2015)
Artifacts produced in the course of electroencephalographic studies (EEG) is a defect of the recording. Modern equipment detects electroencephalographic extremely small values of changes of bioelectric potentials, and therefore the true EEG recording may be distorted due to the impact of various physical (technical) and / or physiological artifacts. Often this makes it very difficult for her explanation and interpretation. The purpose of this article is demonstration of the most typical artifacts that appear during EEG recording to increase the knowledge of doctors conducting EEG study. It is shown that almost all of EEG artifacts have specific (unique) features that allow to experienced doctors separate them from the main record. Therefore, even during the study on the modern diagnostic equipment EEG-technician and doctors must recognize the recorded artifacts, doing its best efforts to remove them from the main recording of EEG.